TGF-βI Regulates Cell Migration through Pluripotent Transcription Factor OCT4 in Endometriosis - Au, Heng-Kien; Chang, Jui-Hung; Wu, Yu-Chih; Kuo, Yung-Che; Chen, Yu-Hsi; Lee, Wei-Chin; Chang, Te-Sheng; Lan, Pei-Chi; Kuo, Hung-Chih; Lee, Kha-Liang; Lee, Mei-Tsu; Tzeng, Chii-Ruey; et al. (PloS one, 2015)
Transforming growth factor (TGF-β)/TGF-β receptor signal is known to promote cell migration. Up-regulation of TGF-β in serum/peritoneal fluid and increased levels of pluripotent transcription factor OCT4 in endometriotic tissues are frequently observed in patients with endometriosis. However, the mechanisms underlying how TGF-β/TGF-β receptor and OCT4 affect endometriotic cell migration still remain largely unknown. Therefore, endometriotic tissue with high cell migratory capacity were collected from patients with adenomyotic myometrium (n = 23) and chocolate cyst (n = 24); and endometrial tissue with low cell migratory capacity in normal endometrium or hyperplastic endometrium (n = 8) were collected as the controls. We found the mRNA levels of TGF-β receptor I (TGF-β RI) and OCT4 were significantly higher in the high-migratory ectopic endometriotic tissues than those of the low-migratory normal or hyperplastic endometrium. Positive correlations between TGF-β RI and OCT4, and either TGF-β RI or OCT4 with migration-related genes (SNAIL, SLUG and TWIST) regarding the mRNA levels were observed in human endometriotic tissues. TGF-βI dose-dependently increased the gene and protein levels of OCT4, SNAIL and N-Cadherin (N-CAD) and silencing of endogenous OCT4 significantly suppressed the TGF-βI-induced expressions of N-CAD and SNAIL in primary human endometriotic stromal cells and human endometrial carcinoma cell lines RL95-2 and HEC1A. Furthermore, TGF-βI significantly increased the migration ability of endometriotic cells and silencing of OCT4 dramatically suppressed the TGF-βI-induced cell migration activity evidenced by wound-closure assay, transwell assay, and confocal image of F-actin cellular distribution. In conclusion, the present findings demonstrate that the niche TGF-β plays a critical role in initiating expressions of pluripotent transcription factor OCT4 which may contribute to the ectopic endometrial growth by stimulating endometrial cell migration. These findings would be useful for developing therapeutic strategies targeting TGF-β-OCT4 signaling to prevent endometriosis in the future.